The psychology of world religions and spiritualities : an indigenous perspective - Sisemore, Timothy A.; Knabb, Joshua J. (Spirituality and mental health, 2020)
"He relationship between psychology and religion has been historically rocky. The trouble is that psychologists often take a "top-down" approach to studying religious beliefs and practices. Consider, for instance, a psychologist who observes a community's religious ceremony and then describes it as a "sociological phenomenon." This strikes members of the community as an attempt to explain away their beliefs. When the sacred experiences of religious followers are treated as nothing more than case studies for journals and textbooks, the full import of their meaning in the hearts and minds of real people is lost. This book corrects that by taking a "bottom-up" approach to understanding religious behavior around the world. Each of the major religions is the focus of a separate chapter, and each chapter is written by a psychologist who is either a practicing member of that religion or who has cultural roots among the people who practice that religion. This gives the reader the intimate perspective of someone who has lived the religion, not merely studied it. Viewing religion in this manner is respectful and conveys all the color, flavor, and idiosyncratic ways that religion animates, inspires, and instructs its adherents. Psychologists in academic and clinical settings desperately need this kind of book today. Across society, we're hearing the call for greater diversity, understanding, and inclusion. With this resource in hand, psychologists will be able to grasp at an intimate level the meaningful role that religion and spirituality plays in the lives of the people they're trying to help"--